RELEVANSI SURAT AN-NAHL AYAT 125 DENGAN METODE BIMBINGAN DAN KONSELING ISLAM - taufik, ismail (AflahConsilia : Jurnal Bimbingan dan Konseling, 2023)
This Article is to find various giudance and counseling methods contained inthe Qur’an as a reference as well as the basis for islamic guidance and counseling. The focus of this research is to explore the islamic guidance and counsling methos contained in Surah an-Nahl ayat 125. The metod usedin this research is atype of library research. The analysis used in this research is contend analysis. These result obtained 3 (three) giudance and counseling methods in Surah an-Nahl ayat 125, the three methods are : 1) al-hikmah method which can be done through assertive communication that can touch the emotional side of the counselee so that he really feels meaningful guidance and counseling service sessions; 2) MauIzatul Hasanah method is how to direct the counselee to be able to apply methods and prespectives in dealing with problems by emulating the attitudes, and thinking framework of role models of Islamic figures such as Prophets, Apostles, Auliya, Ulama, historians and scientist; 3) Mujadalah the implementations of this method through conten mastery supported by expertise in mastering counseling skills and good communication skliss.